HAK WARGA NEGARA UNTUK DILINDUNGI SEBAGAI HAK ASASI MANUSIA DALAM KONSTITUSI - Salahudin Pakaya; Ismet Hadi (At-Tanwir Law Review, 2023)
Protection of citizens has become a basic obligation for the state because citizens have the right to be protected. So that the state does not neglect the protection rights of citizens, the rights of citizens should be set forth in the constitution or the Constitution as the basic law of a country. This constitution is the result of a social contract agreement between citizens and citizens with the government that is empowered to run the country. At least the content of this constitution is the division of powers (authorities) of state institutions, and the most important thing is the statement regarding the rights of citizens which the government must uphold. Indonesia has ratified the Universal Declaration of Human Rights (HAM) and is contained in Law no. 39 of 1999 concerning Human Rights, and Law no. 26 of 2000 concerning the Human Rights Court. But even though regulatory instruments have been made, there is still a legal vacuum that guarantees citizens' constitutional rights as human rights. This is because the human rights court that was formed only examines gross human rights violations, while general or ordinary human rights violations are not the competence of the human rights court.